Laporan Kasus Karsinoma Sel Skuamosa Nasofaring - Cut Vani; Andrian Andrian (Pusat riset dan Inovasi Nasional, 2023)
Nasopharyngeal cancer is a cancer that occurs in the nasopharyngeal mucosa which shows squamous cell differentiation. The nasopharynx is a musculoskeletal and cuboid-shaped tube structure behind the nasal cavity. The cause of nasopharyngeal carcinoma is infection with the Epstein-Barr virus (EBV) and / or Human Papilloma Virus (HPV), with risk factors for smoking, consuming alcohol, genetics, exposure to radiation rays, and decreased body resistance Early detection in KNF cases, with physical examination and support, is expected to provide fast, appropriate and effective treatment as soon as possible, so as to improve cancer survival. A patient Mr.M, a 23-year-old male ca The lump is accompanied by pain and the color of the lump is not reddish. Complaints of swallowing pain and difficulty breathing are denied. Diagnosis of KNF is carried out by anamnesis of clinical symptoms and signs, physical examination, and supporting examinations. Endoscopy can assess abnormalities of the nasopharyngeal mucosa and support biopsy. A biopsy is the definitive way to establish the diagnosis of KNF. Imaging modalities, such as MRI and CT scans, look for tumors that are not visible to the endoscopy and assess tumor extension.